ROSTRUM-LENGTH-TOTAL-LENGTH RELATIONSHIP IN MACROBRACHWM 1DELLA AND M. SCABRfCULUM (DECAPODA, PALAEMONIDAE) - Jayachandran, K V; Balasubramanian, N K (Indian Journal of Fisheries, 2011)
A detailed statistical analysis of the rostrum length-total length relationshipof two species of palaemonicl prawns Macrobrachium idella and M. scabriculumhas been attempted. Two methods, analysis of covariance and body proportionindex methods, were employed. The growth pattern of rostrum in relation to tola'length of M. scabriculum was different in the two sexes whereas it was the samein the case of M. idella.